Pengaruh Media Articulate Storyline Dalam Menggambar Motif Batik Besurek Terhadap Literasi Budaya Siswa Kelas IV Sekolah Dasar - Safitri, Weny; Anggraini, Dwi; Agusdianita, Neza (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of using Articulate Storyline media in the creation of Besurek batik motifs on the cultural literacy of grade IV elementary school students in Bengkulu City. This research used quasi experimental methodology and matching only pretest-posttest control group design. This type of research is quantitative. Based on the results of the study, the data from the pretest and posttest results were significantly different. The average result of the questionnaire before learning in the control class was 35.14 and when the questionnaire after learning rose to 36.25. Meanwhile, the average results of the questionnaire before learning in the experimental class were 42.03 and when the questionnaire after learning rose to 50.21. From this data, it can be seen that the difference between the pretest and posttest, there was a change in results of 9.29. The t test, postest of the control and experimental classes is evidenced by the t value of 4.918 and the Sig value. (2-tailed) of 0.001 with a significance level of 2.004 because the t value < t table (4.918 < 2.004) so that the sig. (2-tailed) < 0.001 then Ha is accepted due to the difference in treatment between the two groups. This means that it can be concluded that there is an effect of Articulate Storyline media in drawing Besurek batik motifs on the cultural literacy of fourth grade elementary school students.